Microfluidic synthesis of GdF3 nanoparticles: Influence of microreaction conditions and dopant ionic radius on the nanoparticle size and scintillation intensity - Ferreira, Carolina Beatriz Brigida Miranda (2024)
X-Ray activated Photodynamic Therapy (XPDT) is a promising cancer treatment that could reduce the patient exposition to ionizing radiation due to the enhanced radiosensitization caused by the photosensitizer (PS) coupled to a nanoscintillator (ScNP). Here, we synthesized and characterized GdF3:Ce3+,Tb3+ nanoparticles for future XPDT applications. Changing the solvent from EG to DEG decreased nanoparticle size from 180 nm to 79 nm while maintaining scintillation intensity (RL). GdF3 nanoparticles with 30% Tb3+ presented strong RL between 475-600 nm. Upon increasing the Tb3+ percentage, a tendency to reduce nanoparticle size was noted, probably due to the ionic substitution of Gd3+ by Tb3+ that may induce a distortion in the crystal lattice, impacting the nanoparticle growth. Surprisingly, 200 nm nanorods became 79 nm spheres after passing through our microfluidic reactor. We attributed the size reduction and morphological change to a thermal breakage process that breaks the large nanorods into smaller spheres due to the rapid expansion-contraction (200°C-25°C) they experience in the microreactor. Adding to the GdF3 30% mol of different lanthanides strongly influenced the nanoparticle size, reducing from 175 nm to 35 nm after the addition of 30%mol of Cerium. GdF3 nanoparticles with 15% Ce3+ and 15% Tb3+ presented a reduced size (70 nm) with enhanced RL intensity. PL results indicated that the superposition of the Ce3+ and Gd3+ energy levels enhances the energy transfer to the luminescent Tb3+ ions, consequently enhancing RL emission. This is the first report on the dual role of Ce3+ in reducing nanoparticle size and enhancing luminescence emission in co-doped GdF3:Ce3+,Tb3+ nanoparticles. These unique properties- reduced nanoparticle size and high radioluminescence-make this co-doped ScNP promising for future applications in XPDT. The enhanced luminescence could improve PS excitation, potentially increasing tumor cell damage.